Alissa Wahid dan Perjuangan RUU PKS: Kiprah Aktivis Perempuan dalam Mendorong Kebijakan Pro-Perempuan - Ragilia Dwi Pradita; Silvana Putri Priageng; Muhammad Sulthan Fatih; Aniqotul Ummah (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
The emergence of the Draft Law on the Elimination of Sexual Violence or RUU PKS is like a breath of fresh air that brings a glimmer of hope that there is a legal umbrella that can protect victims of sexual violence in Indonesia. However, the birth of the RUU PKS has given rise to various responses from the community, some support it and some do not. In pushing for its ratification, activists have emerged who continue to fight for the RUU PKS, one of whom is Alissa Wahid. The purpose of this study is to examine how Alissa Wahid's influence as a female activist in fighting for the RUU PKS as legal protection for victims of sexual violence. The method used is qualitative with the use of literature studies that help research in answering the formulation of the problem well. The results show that through the movement and struggle, Alissa Wahid has opened the eyes of the government and the law in Indonesia to be more on the side of victims of sexual violence, especially women